2010
DOI: 10.1007/s00392-010-0113-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mild hypothermia on hemodynamics in cardiac arrest survivors and isolated failing human myocardium

Abstract: Post-cardiac arrest myocardial dysfunction is a common phenomenon after return of spontaneous circulation (ROSC) and contributes to hemodynamic instability and low survival rates after cardiac arrest. Mild hypothermia for 24 h after ROSC has been shown to significantly improve neurologic recovery and survival rates. In the present study we investigate the influence of therapeutic hypothermia on hemodynamic parameters in resuscitated patients and on contractility in failing human myocardium. We analyzed hemodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
7

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 50 publications
(66 reference statements)
5
40
0
7
Order By: Relevance
“…Although systolic performance is clearly improved at all temperature steps investigated, pronounced hypothermia may impair diastolic function [10]. However, in the temperature range recommended for mild therapeutic hypothermia in cardiac arrest patients (32-34°C) [11,12] , dias tolic function seems to be preserved [6]. Al though mild therapeutic hypothermia may have direct repercussions on the myocardium, a study by Bernard et al showed no clinically signifi cant eff ect on cardiac arrhythmias in the hypothermia group [13].…”
Section: Ild Therapeutic Hypothermiamentioning
confidence: 95%
See 1 more Smart Citation
“…Although systolic performance is clearly improved at all temperature steps investigated, pronounced hypothermia may impair diastolic function [10]. However, in the temperature range recommended for mild therapeutic hypothermia in cardiac arrest patients (32-34°C) [11,12] , dias tolic function seems to be preserved [6]. Al though mild therapeutic hypothermia may have direct repercussions on the myocardium, a study by Bernard et al showed no clinically signifi cant eff ect on cardiac arrhythmias in the hypothermia group [13].…”
Section: Ild Therapeutic Hypothermiamentioning
confidence: 95%
“…Th e phenomenon of increased inotropism during mild therapeutic hypothermia is not associated with increased sarcoplasmic reticulum Ca 2+ -content or increased Ca 2+ -transients [5] . Moreover, recent studies using animal species and in humans have provided accumulating evidence suggesting that mild therapeutic hypothermia may also improve cardiac performance [5,6]. Th erefore, the higher survival rates may also be related to positive hemodynamic eff ects of cooling in patients already suff ering from cardiac disease.…”
Section: Ild Therapeutic Hypothermiamentioning
confidence: 99%
“…In 2006, the National Registry of Cardiopulmonary Resuscitation (CPR) published statistics on 19,819 adults and 524 children with return of spontaneous circulation after cardiac arrest. The mortality rates were 67% among adults and 55% among children (Jacobshagen et al, 2010). Currently, less than half of cardiac arrest patients survive to discharge and less than a third of those discharged have a good neurologic outcome as defined by the Cerebral Performance Category (CPS) Scale (Adler et al, 2011).…”
Section: Epidemiology Of Cardiac Arrestmentioning
confidence: 99%
“…The coiling provides a mechanism to increase surface area, thereby increasing the heat exchange between blood passing over the catheter. Internal cooling and rewarming is much faster and superior to other techniques in tightly regulating target temperature; it is possible to cool patients by 1.46°C -1.59°C per hour (Jacobshagen et al, 2010). A potential advantage of using catheter-based cooling combined with anxiolytics is that it may avoid the need to use paralytics to decrease the shiver seen in surface cooling techniques.…”
Section: Core Cooling 421 Catheter-based Technologiesmentioning
confidence: 99%
See 1 more Smart Citation